Qualifikationsentwicklung der Beschäftigten in Deutschland — eine raumbezogene Analyse - Fromhold-Eisebith, Martina (Raumforschung und Raumordnung | Spatial Research and Planning, 2006)
Based on data provided by the German Institute of Labour Market and Employment Research, the article depicts the development of the qualification structure of employees in German regions between 1993 and 2002, illustrated by maps and figures. We analyse spatial patterns of change for different qualification groups, outlining a regional typology, and discuss issues of ageing as well as differentiations according to types of settlement structure; finally, centre-periphery developments in two selected urban agglomerations are addressed (Berlin and Rhein-Ruhr).